Repeat subcutaneous administration of casirivimab and imdevimab in adults is well-tolerated and prevents the occurrence of COVID-19. (September 2022) - Isa, Flonza; Forleo-Neto, Eduardo; Meyer, Jonathan; Zheng, Wenjun; Rasmussen, Scott; Armas, Danielle; Oshita, Masaru; Brinson, Cynthia; Folkerth, Steven; Faria, Lori; Heirman, Ingeborg; Sarkar, Neena; et al.
Highlights: Phase 1 study assessed monthly casirivimab+imdevimab (CAS+IMD) in uninfected adults Repeat monthly CAS+IMD (1200 mg subcutaneously [SC]) was well-tolerated, with low immunogenicity CAS+IMD (1200 mg SC) showed a substantial risk reduction in COVID-19 occurrence Abstract: Objectives: A phase 1, double-blind, placebo-controlled trial was conducted to evaluate the safety, tolerability, and exploratory efficacy of repeat monthly doses of subcutaneous (SC) casirivimab and imdevimab (CAS+IMD) in uninfected adult volunteers. Methods: Participants were randomized (3:1) to SC CAS+IMD 1200 mg or placebo every 4 weeks for up to six doses. Primary and secondary end points evaluated safety, pharmacokinetics, and immunogenicity. Exploratory efficacy was evaluated by the incidence of COVID-19 or SARS-CoV-2 seroconversion. Results: In total, 969 participants received CAS+IMD. Repeat monthly dosing of SC CAS+IMD led to a 92.4% relative risk reduction in clinically defined COVID-19 compared with placebo (3/729 [0.4%] vs 13/240 [5.4%]; odds ratio 0.07 [95% CI 0.01-0.27]), and a 100% reduction in laboratory-confirmed COVID-19 (0/729 vs 10/240 [4.2%]; odds ratio 0.00). Development of anti-drug antibodies occurred in a small proportion of participants (<5%). No grade ≥3 injection-site reactions (ISRs) or hypersensitivity reactions were reported. Slightly more participants reported treatment-emergent adverse events with CAS+IMD (54.9%) than with placebo (48.3%), a finding that was due to grade 1-2 ISRs. Serious adverse events were rare. No deaths were reported in the 6-month treatment period. Conclusion: Repeat monthly administration of 1200 mg SC CAS+IMD was well-tolerated, demonstrated low immunogenicity, and showed a substantial risk reduction in COVID-19 occurrence. Graphical abstract: Image, graphical abstract